A useful surgical landmark for the trapezio-scaphoid joint - Camillo Fulchignoni; Silvia Pietramala; Chiara Muci; Alessandro El Motassime; Andrea Cruciani; Lorenzo Rocchi; Gianfranco Merendi (Medicinski glasnik, 2026)
Aim: Unintended scaphoid excision is a rare but serious complication that can occur during surgical procedures involving the trapezium, including but not limited to trapeziectomy. Although prosthetic replacement is increasingly favored in the treatment of rhizarthrosis, trapeziectomy (with or without ligamentoplasty) remains a widely used and effective option. To reduce the risk of inadvertently removing the scaphoid, we rely on the anatomical intersection between the radial artery branch and the first dorsal compartment tendons as a landmark for identifying the scapho-trapezial joint. Methods: In our Institutiton the, Policlinico Universitario A. Gemelli IRCSS, we have been using a simple landmark to identify scapho-trapezial joint to teach residents: during surgery, after isolating the radial artery, a 16G needle is inserted at the intersection of the extensor tendons and the radial artery branch, followed by fluoroscopy to confirm needle placement in the scapho-trapezial joint. Patients were classified according to Eaton-Littler classification and the accuracy of the Landmark was then assessed among groups. Results: So far we used the landmark on 212 patients. The distribution by Eaton-Littler stage was: 11 stage 1, 63 stage 2, 79 stage 3, and 33 stage 4. The reference point was accurate in 178 cases. No significant differences were found by sexgender or between stages 1, 2 and 3. However, accuracy in stage 4 was significantly lower (p<0.00001). Conclusion: Our results confirm the reliability of this reference point, particularly in stages 1-3. While useful in stage 4, additional caution is required due to slightly reduced precision.
Keywords: c05 muskoskeletal diseases; E01 diagnosis; E04 surgical procedures